Strengthening Tolerance and Social Integration in Susuru Hamlet, Kertajaya Village (Preserving Harmony in Diversity) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Susuru Hamlet in Kertajaya Village is a multireligious community comprising Muslims, Catholics, Protestants, and adherents of Sunda Wiwitan. This religious plurality calls for the contextual strengthening of tolerance and social integration based on community participation. This study aims to describe and analyze the implementation of interfaith collaboration programs using the Participatory Action Research (PAR) approach. The method was conducted in three stages: problem identification, collaborative program implementation, and participatory reflection and evaluation. Two main programs were carried out: a joint interfaith clean-up at the public cemetery (TPU) and economic skills training for PKK (Family Welfare Empowerment) members from different religious backgrounds. The findings reveal that these activities increased community members’ capacity to engage in inclusive interactions, fostered mutual understanding, and strengthened social cohesion. Local values such as gotong royong (mutual cooperation), silih asih (compassion), and tumarima (acceptance) emerged as key drivers of harmony. These values facilitated interfaith solidarity without undermining individual beliefs. The study concludes that participatory and local wisdom-based approaches are effective in fostering grassroots tolerance and can serve as a replicable model for other diverse communities. The implications suggest the need for policy frameworks that support bottom-up peacebuilding and the institutional strengthening of community initiatives in multifaith settings.